Three Cases with Visual Hallucinations following Combined Ocular and Occipital Damage - Bogusław Paradowski; Edyta Kowalczyk; Justyna Chojdak-Łukasiewicz; Aleksandra Loster-Niewińska; Monika Służewska-Niedźwiedź (Case Reports in Medicine)
Charles Bonnet syndrome is an underrecognized disease that involves visual hallucinations in visually impaired patients. We present the cases of three patients who experienced complex visual hallucinations following various pathomechanisms. In two cases, diagnosis showed coexistence of occipital lobe damage with ocular damage, while in the third case it showed occipital lobe damage with retrobulbar optic neuritis. Theories of pathogenesis and the neuroanatomical basis of complex visual hallucinations are discussed and supported by literature review.